1979
DOI: 10.1042/bj1770283
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of isoenzymes of glycerol phosphate acyltransferase

Abstract: Subcellular-fractionation studies confirmed previous findings that rat liver glycerol phosphate acyltransferase was located in both mitochondria and the microsomal fraction. Studies of the two activities revealed several differences between them. The mitochondrial enzyme had a lower Km for sn-glycerol 3-phosphate and was more resistant to heat inactivation than was the microsomal enzyme. Some preparations of the mitochondrial enzyme were inhibited by high concentrations of glycerol phosphate. The mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Finding that GPAT4 localizes to LDs raised an apparent contradiction as members of the GPAT/AGPAT enzyme family had been reported as ER enzymes based on their cofractionation with microsomes (Aguado and Campbell, 1998; Coleman and Lee, 2004; Nimmo, 1979). To address this question, we localized GPAT4 and an ER marker (N-terminally GFP-tagged SEC61β).…”
Section: Resultsmentioning
confidence: 99%
“…Finding that GPAT4 localizes to LDs raised an apparent contradiction as members of the GPAT/AGPAT enzyme family had been reported as ER enzymes based on their cofractionation with microsomes (Aguado and Campbell, 1998; Coleman and Lee, 2004; Nimmo, 1979). To address this question, we localized GPAT4 and an ER marker (N-terminally GFP-tagged SEC61β).…”
Section: Resultsmentioning
confidence: 99%
“…It is remarkable, however, that the phenotypes of GPAT1 knock-out mice occur, even though ?60% of wild-type activity is provided by GPAT2 in the mitochondria. In adipose tissue and liver of normal rats, GPAT2 is likely only a minor component of total GPAT activity, since careful fractionation studies in these tissues have shown ,10% NEM-sensitive GPAT activity associated with mitochondria (27)(28)(29)(30). However, it is important to keep in mind that GPAT2 may contribute more significantly to total GPAT activity in other tissues and that measurement of NEM-sensitive GPAT activity in unfractionated tissues may assess mitochondrial GPAT2 in addition to microsomal GPAT isoforms.…”
Section: Mitochondrial Nem-sensitive Gpat (Gpat2)mentioning
confidence: 99%
“…These studies found that the mitochondrial isoform accounts for ?50% of total GPAT activity in rat liver and is significantly decreased upon fasting (27,28). The microsomal isoform is the major isoform in brown and white adipose tissue, accounting for 80-90% of total GPAT activity (29,30), and is dramatically upregulated during adipocyte differentiation (16,31,32).…”
Section: Tissue Distribution and Regulation Of Gpat Isoforms As Definmentioning
confidence: 99%
“…The distribution of GPAT isoforms varies greatly from tissue to tissue. In the liver, mitochondrial GPAT1 accounts for 50% of GPAT activity ( 39,40 ) whereas in heart, white adipose tissue, and brown adipose tissue, microsomal GPAT activity (GPAT 3 and 4) accounts for most of the activity ( 9,10,41,42 ). In contrast, in skeletal muscle, greater than 90% of GPAT activity is accounted for by GPAT1 ( 43 ).…”
Section: Activation Of Ppars Transactivates Gpat3 Gene Expressionmentioning
confidence: 97%